Stunting Control in Bendo, Sukodono, Sragen, Central Java: Pengendalian Stunting di Desa Bendo, Sukodono, Sragen, Jawa Tengah - Akhmad Mustofa; Nanik Suhartatik (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2024)
Stunting in the Sukodono Sragen area in Central Java in 2023 reached 17.5% or consisted of 308 children with stunting. This sub-district has the second largest number of stunted children in Sragen Regency. Bendo Village is one of the villages in Sukodono Sub-district with 20 stunted children. This service aims to observe the effectiveness of the implementation of the PMT (Supplementary Feeding) program carried out in Bendo village by the Puskesmas Sukodono. The observation method carried out is weighing and measuring the height of each toddler with stunting every 10 (ten) days for 3 months the PMT program is run. The results showed that the provision of PMT did not have a significant impact on changes in the number of stunting sufferers in Bendo village Sukodono Sragen.